Single-cell mass distributions reveal simple rules for achieving steady-state growth - Benjamin R. K. Roller; Cathrine Hellerschmied; Yanqi Wu; Teemu P. Miettinen; Annika L. Gomez; Scott R. Manalis; Martin F. Polz (mBio, 2023)
ABSTRACT Optical density is a proxy of total biomass concentration and is commonly used for measuring the growth of bacterial cultures. However, there is a misconception that exponential optical density growth is equivalent to steady-state population growth. Many cells comprise a culture and individuals can differ from one another. Hallmarks of steady-state population growth are stable frequency distributions of cellular properties over time, something total biomass growth alone cannot quantify. Using single-cell mass sensors paired with optical density measurements, we explore when steady-state population growth prevails in typical batch cultures. We find the average cell mass of Escherichia coli and Vibrio cyclitrophicus growing in several media increases by 0.5–1 orders of magnitude within a few hours of inoculation, and that time-invariant mass distributions are only achieved for short periods when cultures are inoculated with low initial biomass concentrations from overnight cultures. These species achieve an effective steady-state after approximately 2.5–4 total biomass doublings in rich media, which can be decomposed to 1 doubling of cell number and 1.5–3 doublings of average cell mass. We also show that typical batch cultures in rich media depart steady-state early in their growth curves at low cell and biomass concentrations. Achieving steady-state population growth in batch culture is a delicate balancing act, so we provide general guidance for commonly used rich media. Quantifying single-cell mass outside of steady-state population growth is an important first step toward understanding how microbes grow in their natural context, where fluctuations pervade at the scale of individuals. IMPORTANCE Microbiologists have watched clear liquid turn cloudy for over 100 years. While the cloudiness of a culture is proportional to its total biomass, growth rates from optical density measurements are challenging to interpret when cells change size. Many bacteria adjust their size at different steady-state growth rates, but also when shifting between starvation and growth. Optical density cannot disentangle how mass is distributed among cells. Here, we use single-cell mass measurements to demonstrate that a population of cells in batch culture achieves a stable mass distribution for only a short period of time. Achieving steady-state growth in rich medium requires low initial biomass concentrations and enough time for individual cell mass accumulation and cell number increase via cell division to balance out. Steady-state growth is important for reliable cell mass distributions and experimental reproducibility. We discuss how mass variation outside of steady-state can impact physiology, ecology, and evolution experiments.